2021
DOI: 10.1152/jn.00012.2021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of pointing and visual localization in depth around the natural grasping distance

Abstract: Vision in depth is distorted. A similar distortion can be observed for pointing to visual targets in depth. It has been suggested that pointing errors in depth reflect the visual distortion. Alternatively, pointing in depth might be guided by a prior that biases movements toward the natural grasping distance at which object manipulation is usually performed. To dissociate whether pointing is guided by distorted vision only or whether it takes into account a natural grasping distance prior, we adapted pointing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, studies on cataract-treated participants showed the restoration of visual object recognition ( Held et al, 2011 ; Chen et al, 2016 ) and the acquisition of multisensory integration ( Senna et al, 2021 ) is possible within a brief period after surgery by exploiting the cross-modal interactions between vision and touch. The haptic and visual recalibration is also visible in adults following visuomotor adaptation tasks ( Volcic et al, 2013 ; Wiesing et al, 2021 ), which might be related to the strong couplings that exist between the senses and movement control ( Steinbach and Held, 1968 ; Bock, 1987 ; Maiello et al, 2018 ). Our results complement these findings and raise the intriguing possibility that the haptic modality available during sensorimotor interactions with the environment could be effective in learning or restoring visuomotor functions during development and throughout the lifespan.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, studies on cataract-treated participants showed the restoration of visual object recognition ( Held et al, 2011 ; Chen et al, 2016 ) and the acquisition of multisensory integration ( Senna et al, 2021 ) is possible within a brief period after surgery by exploiting the cross-modal interactions between vision and touch. The haptic and visual recalibration is also visible in adults following visuomotor adaptation tasks ( Volcic et al, 2013 ; Wiesing et al, 2021 ), which might be related to the strong couplings that exist between the senses and movement control ( Steinbach and Held, 1968 ; Bock, 1987 ; Maiello et al, 2018 ). Our results complement these findings and raise the intriguing possibility that the haptic modality available during sensorimotor interactions with the environment could be effective in learning or restoring visuomotor functions during development and throughout the lifespan.…”
Section: Discussionmentioning
confidence: 97%
“…Participants were more accurate pointing at targets that appeared further away from their body than the targets that appeared close to them to determine reachability. One possible reason for this could be the observed utility for pointing movements toward the natural grasping distance (i.e., pointing gestures that require the participant to extend their arm to maximum arm length) as opposed to movements away from the natural grasping distance (Wiesing et al., 2021). This would mean that pointing judgments would be more accurate for targets that appeared at or beyond reach and biased within reach.…”
Section: Discussionmentioning
confidence: 99%
“…is calculation method based on the recurrent neural network has been widely used in speech recognition, natural language processing, stock evaluation, and other issues [41][42][43].…”
Section: Neural Network Algorithm and Computermentioning
confidence: 99%